2011
DOI: 10.1097/mop.0b013e328346198f
|View full text |Cite
|
Sign up to set email alerts
|

Critical care of the pediatric patient with rheumatic disease

Abstract: Here we discuss the complications of childhood rheumatic conditions that necessitate critical intervention. We discuss how improved understanding of the cellular and molecular basis of disease pathogenesis holds the promise of more targeted therapy without the adverse effects of global immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The prognosis related to the age, poor prior chronic health status, earlier critical care unit admission, infection, and immunosuppressive treatment [[7], [8], [9]]. Unfortunately, the available published data about children with rheumatic diseases admitted to intensive care unit is very limited [10,11]. Furthermore, we are not aware about any published data from the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis related to the age, poor prior chronic health status, earlier critical care unit admission, infection, and immunosuppressive treatment [[7], [8], [9]]. Unfortunately, the available published data about children with rheumatic diseases admitted to intensive care unit is very limited [10,11]. Furthermore, we are not aware about any published data from the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…Because the 3 patients we describe who died of CVC-related bacterial sepsis manifested unusually severe and rapidly progressing multiorgan failure, we considered the possibility of MAS in the differential diagnoses ( 14 , 16 , 33 , 34 ). MAS is a well-recognized major risk factor for death in children with JIA admitted to PICU ( 33 , 34 ). A recent international study of a large cohort of So-JIA patients identified the most common clinical features as fever, organomegaly, central nervous system involvement, and hemorrhage ( 16 ).…”
Section: Possible Risk Factors For Severe Infection and Deathmentioning
confidence: 99%
“…6 The main cause of mortality in pediatric patients with AIDs admitted to the ICU is severe infection. 7 However, prognosis in pediatric patients is dependent on the presence of infection as well as AIDs disease severity level during their PICU stay. Thus, a multidisciplinary approach to care is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a multidisciplinary approach to care is needed. 7 In Latin America, limited data exist on understanding the course of pediatric AIDs. This study aims to characterize the main causes of PICU admission in pediatric patients with AIDs at a tertiary health hospital in Cali, Colombia, and describe associated risk factors, complications, and outcomes among this patient population.…”
Section: Introductionmentioning
confidence: 99%